Diagnostic imaging methods and surgical treatments for intestinal malrotation in the pediatric population: An integrative review (Research, Society and Development, 2024)
Intestinal malrotation is a congenital anomaly characterized by incomplete or abnormal intestinal rotation during embryonic development, leading to various complications such as intestinal volvulus and obstructions. This review aimed to analyze different diagnostic imaging modalities used to identify intestinal malrotation in pediatric patients, assessing their advantages, limitations, and contributions to early and accurate diagnosis. The study is based on a literature review of techniques such as ultrasonography, computed tomography (CT) scans, and contrast-enhanced upper gastrointestinal (UGI) series. Databases including Virtual Health Library (VHL), PubMed, and Google Scholar were searched using the descriptors “intestinal malrotation”, “diagnostic imaging”, and “intestinal volvulus”. Results indicate that ultrasonography is the first-line diagnostic tool due to its non-invasive nature and high effectiveness in identifying volvulus, especially in children. However, computed tomography (CT) scans provide a more detailed evaluation of mesenteric anatomy and are recommended when ultrasonography is inconclusive. Contrast-enhanced UGI series remain the gold standard for confirming malrotation. It is concluded that the integrated use of these imaging modalities is essential for precise and rapid diagnosis, facilitating the selection of appropriate surgical treatment, such as the Ladd procedure, which corrects malrotation and prevents severe complications like intestinal ischemia.